2020
DOI: 10.3389/fnagi.2020.00044
|View full text |Cite
|
Sign up to set email alerts
|

The Apolipoprotein E ε4 Allele-Dependent Relationship Between Serum Lipid Levels and Cognitive Function: A Population-Based Cross-sectional Study

Abstract: Frontiers in Aging Neuroscience | www.frontiersin.org March 2020 | Volume 12 | Article 44Wei et al. APOE Genotype, Lipids and CognitionConclusions: APOE ε4 carriers, but not non-carriers, with lower serum high-density lipoprotein had a higher prevalence of cognitive impairment and a lower Mini-Mental State Examination score. These results suggest that the APOE ε4 allele may affect the relationship between serum lipid levels and cognitive impairment. However, the specific mechanism needs to be further elucidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…Cholesterol metabolism may also play an essential role in the pathophysiology of AD [ 14 ]. From human epidemiological studies, high levels of total cholesterol in serum could influence the processing of amyloid precursor protein (APP) in neurons, thereby increasing the risk for AD [ 15 , 16 , 17 ]. The activity of β- and γ-secretase complexes involved in APP cleavage depends on cholesterol metabolism [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol metabolism may also play an essential role in the pathophysiology of AD [ 14 ]. From human epidemiological studies, high levels of total cholesterol in serum could influence the processing of amyloid precursor protein (APP) in neurons, thereby increasing the risk for AD [ 15 , 16 , 17 ]. The activity of β- and γ-secretase complexes involved in APP cleavage depends on cholesterol metabolism [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another explanation could be the bias due to the lost follow-up of ε4 carriers due to CVD diseases in the high LDL-C group. Five among seven studies in a review detected no interaction between APOE ε4 and TC (Anstey et al, 2008), while some studies found the effect of cholesterol varied in APOE ε4 carriers and non-carriers (Hall et al, 2006;Wei et al, 2020). Possible explanations for the inconsistent results may be the differences in sample size, ethnicity, age, and other population characteristics.…”
Section: Discussionmentioning
confidence: 97%
“…A meta-analysis in 2007 pooling 72,150 participants from 22 studies demonstrated an obvious increase trend of TC and LDL-C in the order of APOE ε2ε2, ε2ε3, ε3ε3, ε3ε4, and ε4ε4 (Bennet et al, 2007). In the Chinese population, studies also found APOE ε2 carriers had lower TC and LDL-C than APOE ε2 non-carriers (Kang et al, 2016), and APOE ε4 carriers had higher serum TC, TG, and LDL levels and lower HDL levels than APOE ε4 non-carriers (Wei et al, 2020). In addition, age was also negatively associated with TC.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, peripheral serum levels of lipids have been associated with AD and cognitive impairment by an allele of APOE . However, emerging studies in mammals have suggested that specific alterations in fat profiles and even elevated fat storage can be associated with longevity [ 62 , 63 ].…”
Section: Protein Network Regulate Homeostasis To Influence Lifespanmentioning
confidence: 99%